(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article deals with the analysis of some verbs which represent natural phenomena in English and the appropriate translations in Uzbek language by analyzing comparatively according to their grammatical and lexical features.